2012
DOI: 10.1051/0004-6361/201118738
|View full text |Cite
|
Sign up to set email alerts
|

The quest for complex molecules in space: laboratory spectroscopy ofn-butyl cyanide,n-C4H9CN, in the millimeter wave region and its astronomical search in Sagittarius B2(N)

Abstract: Context. The saturated n-propyl cyanide was recently detected in Sagittarius B2(N). The next largest unbranched alkyl cyanide is n-butyl cyanide. Aims. We provide accurate rest frequency predictions beyond the millimeter wave range to search for this molecule in the Galactic center source Sagittarius B2(N) and facilitate its detection in space. Methods. We investigated the laboratory rotational spectrum of n-butyl cyanide between 75 GHz and 348 GHz. We searched for emission lines produced by the molecule in ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Upper limits to the column densities of glycine (NH 2 CH 2 COOH), methoxyacetonitrile (CH 3 OCH 2 CN), 2-cyanoethanol (HOCH 2 CH 2 CN), 2-aminopropionitrile (CH 3 CH(NH 2 )CN), and n-butyl cyanide (n-C 4 H 9 CN) based on our spectral survey of Sgr B2(N) were reported elsewhere Braakman et al 2010;Møllendal et al 2012;Ordu et al 2012). In this section, we list a few additional upper limits derived from our survey for species that were either claimed to be detected toward Sgr B2(N) by other authors, or that are of some interest for astrochemistry.…”
Section: Non-detectionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Upper limits to the column densities of glycine (NH 2 CH 2 COOH), methoxyacetonitrile (CH 3 OCH 2 CN), 2-cyanoethanol (HOCH 2 CH 2 CN), 2-aminopropionitrile (CH 3 CH(NH 2 )CN), and n-butyl cyanide (n-C 4 H 9 CN) based on our spectral survey of Sgr B2(N) were reported elsewhere Braakman et al 2010;Møllendal et al 2012;Ordu et al 2012). In this section, we list a few additional upper limits derived from our survey for species that were either claimed to be detected toward Sgr B2(N) by other authors, or that are of some interest for astrochemistry.…”
Section: Non-detectionsmentioning
confidence: 77%
“…The main goal of the survey was to search for new complex organic molecules in the gas phase of the interstellar medium. This has been partially addressed in a number of earlier publications (Belloche et al , 2009Müller et al 2008;Brünken et al 2010;Braakman et al 2010;Møllendal et al 2012;Ordu et al 2012). This article now presents the complete analysis of the full survey, the main goal being to provide a reliable identification of the detected lines.…”
Section: Introductionmentioning
confidence: 99%
“…Several spectroscopic investigations were performed in support of this study, for example on iso-propyl cyanide (Müller et al 2011), anti-ethanol with one 13 C (Bouchez et al 2012), 2-aminopropionitrile (Møllendal et al 2012), and n-butyl cyanide (Ordu et al 2012). In addition, a number of spectroscopic studies have been prompted by the results of these line surveys, for example, on methyleneaminoacetonitrile (Motiyenko et al 2013), aminoacetonitrile (Motoki et al 2013), and 1,2-propanediol (Bossa et al 2014).…”
Section: Introductionmentioning
confidence: 62%
“…This measurement has been extended to the shorter millimeter wavelengths to aid its astronomical searches. The radio-astronomical searches for n-butyl cyanide in the Sagittarius B2(N) molecular cloud yielded only upper limits of its column density without any successful detection [31]. This is the only isomer of the C 5 H 9 N isomeric group that has been astronomically searched for though it is not the most stable molecule of the group.…”
Section: Resultsmentioning
confidence: 99%
“…According to their experiment, the next three conformers are AA (30%), AG (13%) and GG' (11%). According [31], n-butyl cyanide could exist into five conformers. Ordu et al (2012) and references therein showed that AA is the most stable conformer and GG being the highest energy conformer.…”
Section: N-butyl Cyanidementioning
confidence: 99%